European Journal of Clinical Nutrition - Soares, Mario; Mueller, Manfred J.; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Springer Nature.)
The European Journal of Clinical Nutrition is an international, peer-reviewed journal covering all aspects of human and clinical nutrition. The journal welcomes original research, reviews, clinical case reports and short communications based on clinical, metabolic and epidemiological studies that describe methodologies, mechanisms, associations and benefits of nutritional interventions for clinical disease and health promotion.
Keywords: Medicine; Public health; Internal medicine; Metabolic diseases; Clinical nutrition; Epidemiology; Medicine/Public Health, general; Public Health; Epidemiology; Internal Medicine; Clinical Nutrition; Metabolic Diseases